2020
DOI: 10.1021/acs.jmedchem.0c01246
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the In Vivo Potency of Pyrazolopyrimidine MALT1 Protease Inhibitors by Reducing Metabolism and Increasing Potency in Whole Blood

Abstract: The paracaspase MALT1 has gained increasing interest as a target for the treatment of subsets of lymphomas as well as autoimmune diseases, and there is a need for suitable compounds to explore the therapeutic potential of this target. Here, we report the optimization of the in vivo potency of pyrazolopyrimidines, a class of highly selective allosteric MALT1 inhibitors. High doses of the initial lead compound led to tumor stasis in an activated B-cell-like (ABC) diffuse large B-cell lymphoma (DLBCL) xenograft m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 48 publications
1
11
0
1
Order By: Relevance
“…In line with previous reports, MLT-985 was slightly more potent (two- to threefold) than MLT-943 in inhibiting constitutive MALT1 protease activity in TRAF6 KO Jurkat T cells (Fig. 7A) ( 37 ). Compared with MLT-943, MLT-985 displayed superior pharmacokinetics and improved bioavailability in mice ( 37 ) and therefore was chosen to achieve effective inhibition of chronic MALT1 activity in vivo.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In line with previous reports, MLT-985 was slightly more potent (two- to threefold) than MLT-943 in inhibiting constitutive MALT1 protease activity in TRAF6 KO Jurkat T cells (Fig. 7A) ( 37 ). Compared with MLT-943, MLT-985 displayed superior pharmacokinetics and improved bioavailability in mice ( 37 ) and therefore was chosen to achieve effective inhibition of chronic MALT1 activity in vivo.…”
Section: Resultssupporting
confidence: 92%
“…We asked whether pharmacologic inhibition of constitutive MALT1 protease activation is able to ameliorate uncontrolled immune activation resulting from T cell–specific TRAF6 ablation. We evaluated inhibition of constitutive MALT1 protease activity by MLT-943 and MLT-985, two potent MALT1 inhibitors ( 28 , 37 ). In line with previous reports, MLT-985 was slightly more potent (two- to threefold) than MLT-943 in inhibiting constitutive MALT1 protease activity in TRAF6 KO Jurkat T cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For stimulation of primary T cells, cells were transferred to anti-CD3 (0.5 µg/ml) pre-coated 96-well plates and stimulated in the presence of soluble anti-CD28 and anti-mouse IgG1/IgG2a as described above. Inhibitor treatment was done with 25 μM proteasome inhibitor MG132 (1 h pre-treatment; Calbiochem), 1 μM MALT1 inhibitor MLT-985 [ 32 ] (4 h pre-treatment), 75 μM MALT1 inhibitor Z-VRPR-FMK (Enzo Life Sciences) (3 h pre-treatment) and 2.5 μM cIAP1/2 inhibitor birinapant (10 min pre-treatment; BioCat) solved in dimethylsulphoxide (DMSO).…”
Section: Methodsmentioning
confidence: 99%
“…However, the structures of these two compounds are very similar to that of 4 . Among these two compounds, MLT-985 effectively led to tumor regression in an ABC-DLBCL lymphoma xenograft model. , In 2018, Lorena et al reported a z-VRPR-FMK derivative 5 as a substrate-mimetic peptidic covalent MALT1 inhibitor. This compound showed maximal inhibition of MALT1 activity in in vitro and cell-based assays.…”
Section: Introductionmentioning
confidence: 99%